Pemanfaatan Aplikasi Telegram sebagai Media Komunikasi dan Informasi Tim penjualan & pemasaran CV Ardent Furnitur - Suminto, Miftahul Adi Suminto; Hariadi Yutanto (Universitas Negeri Surabaya, 2025)
This study explores the benefits of the Telegram application as a communication and information medium for the Sales and Marketing team at CV Ardent Furniture. Effective communication is essential for producing, distributing, and disseminating information, particularly in today's digital age, where various platforms such as WhatsApp, email, and online meeting rooms are commonly used. Telegram stands out due to its user-friendly interface and diverse features, making it a valuable tool for the sales and marketing team. This research aims to analyse the communication patterns among team members using Telegram, highlighting how it facilitates quick information exchange. The application enables the sharing of images, videos, voice messages, and documents, thereby enhancing collaboration and participation among team members. Utilising qualitative methods and an interpretive descriptive approach, the study examines interaction patterns within Telegram groups and the intensity of information exchange, demonstrating how this platform supports the operational needs of the Sales and Marketing department at CV Ardent Furniture.